The Role of CD64 and CRP in the Diagnosis of Sepsis in Neonates (American Journal of Life Science and Innovation, 2025)
Sepsis is the body’s extensive reaction to an infection. It is a severe medical emergency. Without prompt treatment, sepsis can quickly lead to tissue damage, organ failure, and death. Neonatal sepsis is defined as a syndrome of clinical features of the spread of infection and the presence of bacteremia increase access to the bloodstream. Bacteria most often cause infantile septicemia. An infant may be exposed to infections in the hospital or at home. This work came to assess the role of CRP and neutrophil CD64 in the diagnosis of sepsis in neonates and infants. This study is a case-control study, it involved two groups (60) patients and (20) controls of one day to one year of age during the period from May 2019 to September 2020 of neonates and infants admitted in Kerbala pediatric teaching hospital and Kerbala Primary health care centers. For a total of 80 children, two categories have been included and classified. the study showed the mean age for neonates of sepsis was (7.40±13) days while the mean age for neonates of control was (5.58±6.75)days, The mean age for infants of sepsis was (4.1±7.971) months while the mean age for infants of control was (4.01±5.66) months. in this research, CRP, PCT, and nCD64 are well-diagnostic biomarkers for early detection of neonatal and infantile sepsis. The combination of these biomarkers the diagnosis of suspected early and late-onset neonatal sepsis based on ROC curve analysis.